Understanding photography : master your digital camera and capture that perfect photo - McHugh, Sean (Sean T.) (No Starch Press, Inc., 2019)
"Teaches the core concepts that underlie digital photography with highly visual and comprehensive explanations. Topics covered include the fundamentals of exposure, how lens choice affects creative control, digital image characteristics, and how to make the most of natural light"--Provided by publisher.